Implementasi Erp Packet Tracker Pada Shopee Express Cabang Telanaipura Jambi: - - Putri Nazwa, Nesha (LPPM Universitas Dinamika Bangsa, 2025)
Logistic companies are currently facing significant challenges in meeting the ever-increasing customer demands,particularly in terms of speed and transparency of delivery services. PT. Shopee Express Telanaipura Jambi branch hasencountered various issues, including customer complaints about difficulties in tracking packages and slow operationalprocesses. These problems have negatively impacted operational efficiency and customer satisfaction. This research aims todesign an implementation of an Enterprise Resource Planning (ERP) system that can integrate real-time package tracking andoptimize delivery routes. The research methodology employed includes observation, interviews, and system design. Theexpected outcome of this plan is the creation of a more efficient workflow, a reduction in operational errors through a moretransparent tracking system, and an increase in customer satisfaction. The ERP implementation plan is designed as a strategicstep to strengthen Shopee Express's competitiveness in the logistics industry.